The role of self efficacy in forming prosocial personality through the viewing of Islamic based films - Rosmawati Mohamad Rasit (Universiti Kebangsaan Malaysia, 2013)
Pro-social personality can be associated with the positive behaviours that are commonly practised in the socio-surrounding of a cultured community. For example the action of helping, loving and empathy development with each other. Through the viewing of the Islamic based films, this study was looking at the opportunity in forming the values of pro-social that are seen parallel with the religion (Islam) itself. The study was also analysing the importance of the self-efficacy factors towards the pro-social personality among the audience who were watching the Islamic based films. Therefore, the audience also needs to have good self-efficacy level in choosing the films genre that they will be watching. Hence, the study was conducted to analyse the role of the self-efficacy as the mediating factor that can control the formation of the pro-social personality through watching the Islamic based films. The study used survey method. There were 1028 respondents chosen randomly through the stratified random sampling technique within 6 institutions from the Public Higher Education Institution in the Klang Valley. Data were collected through the distribution of questionnaire and were analysed by using descriptive analysis and partial correlational test. The study found out that the interest level towards watching Islamic based films was high and the partial correlation test established the results of the self-efficacy factor was controlled as the controlled variable. There was also a positive significant relationship between watching the Islamic based films and the prosocial personality. The study also showed that the self efficacy as the mediator has a significant relationship with the formation of the prosocial personality.